Virtual Instrumentation Based Active Fin Control for Roll Stabilization - Subramanian, V Anantha; Asokumar, G; Mohamed, Thaju (Journal of Naval Architecture and Marine Engineering, 2009)
The objective of this work is to develop a non-traditional strategy for providing control of ship roll motion in a seaway using active fins. This is based on a multidisciplinary approach. It consists of the assessment of the hydrodynamic coefficients of a ship using a numerical package [SEDOS], representation of the hydrodynamic coefficients by suitable polynomial functions, identification of the time dependent fundamental frequency in the roll disturbance signal sample, generation of control signal for an appropriate fin angle based on the fin lift characteristics of the chosen fin and employment of feedback control to maintain the fin at the appropriate angle for maximum control. Once the ship based hydrodynamic coefficients are generated, the entire control algorithm is developed in the virtual instrumentation mode using LabVIEW environment. One of the disadvantages of the traditional stabilizer system is the enormous hardware involved in the controllers and instrumentation panels, which makes maintenance and troubleshooting difficult. With the help of virtual instrumentation, design of the stabilization controller and instrumentation panels can be carried out much more effectively, in comparison with the traditional hardware approach. Key words: Roll stabilization, Active fin control, Virtual instrumentation doi:10.3329/jname.v2i2.1869 Â Journal of Naval Architecture and Marine Engineering 2(2005) 11-24